2016
DOI: 10.1007/s00432-016-2286-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel microvascular invasion-based prognostic nomograms to predict survival outcomes in patients after R0 resection for hepatocellular carcinoma

Abstract: The novel classification system of MVI and the nomograms enabled more accurate predictions of risk of tumor recurrence and overall survival in patients with HCC after R0 liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 24 publications
2
101
2
Order By: Relevance
“…The presence of MVI has been confirmed to be associated with intrahepatic metastasis, and the risk of MVI increasing with tumor size and tumor numbers . Literatures had showed that MVI was detected in 15.0%‐57.1% of HCC, and 60%‐90% of tumor sizes greater than 5 cm .…”
Section: Discussionmentioning
confidence: 93%
“…The presence of MVI has been confirmed to be associated with intrahepatic metastasis, and the risk of MVI increasing with tumor size and tumor numbers . Literatures had showed that MVI was detected in 15.0%‐57.1% of HCC, and 60%‐90% of tumor sizes greater than 5 cm .…”
Section: Discussionmentioning
confidence: 93%
“…However, this referenced study did not consider differences in baseline characteristics, which might influence the prognosis analysis . In addition, the presence of MVI is widely reported to be a significant prognostic factor for HCC . Even for patients with small HCCs up to 3 cm, MVI enhances the rate of tumor recurrence and dramatically shortens long‐term survival .…”
Section: Introductionmentioning
confidence: 98%
“…8 In addition, the presence of MVI is widely reported to be a significant prognostic factor for HCC. [9][10][11] Even for patients with small HCCs up to 3 cm, MVI enhances the rate of tumor recurrence and dramatically shortens long-term survival. 12,13 Meanwhile, the tumor biology and condition of the underlying liver, instead of tumor size, were determined to be better indicators of the prognosis and should be given more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed that vascular invasion is an independent risk factor for the prognosis of HCC patients who underwent surgical treatment [22][23][24]. The presence of vascular invasion of the portal or hepatic veins is associated with a high risk of tumour recurrence and is regarded as a prerequisite for systemic tumour dissemination [25,26].…”
Section: Discussionmentioning
confidence: 99%